Integrated pest management for crops and pastures - Horne, Paul A. (Paul Anthony), 1956-.; Page, Jessica (Collingwood, Vic. : Landlinks, 2008)
This book describes in straightforward language what is required for farmers to successfully implement Integrated Pest Management (IPM) in cropping and grazing operations.
Keywords: Agricultural pests -- Integrated control -- Australia; Crops -- Diseases and pests -- Integrated control; Pastures -- Diseases and pests -- Integrated control